Massive circumpolar biomass of Southern Ocean zooplankton: Implications for food web structure, carbon export, and marine spatial planning - Guang Yang; Angus Atkinson; Evgeny A. Pakhomov; Simeon L. Hill; Marie‐Fanny Racault (Limnology and Oceanography, 2022)
With rapid, sector‐specific climatic changes impacting the Southern Ocean, we need circumpolar‐scale biomass data of its plankton taxa to improve food web models, blue carbon budgets and resource management. Here, we provide a new dataset on mesozooplankton biomass with 2909 records spanning the last 90 yr, and describe, in comparable carbon units, their circumpolar distribution alongside those of phytoplankton, Antarctic krill, and salps. With our datasets, we estimate total summer carbon biomasses for phytoplankton (36 MT), mesozooplankton (67 MT), krill (30 MT), and salps (1.7 MT). The mesozooplankton value is much higher than previously reported and, added to that of krill and salps, points to an enormous overall biomass of zooplankton in the Southern Ocean. This means that the pyramids of biomass are often inverted, with higher biomass of zooplankton than of phytoplankton. Such high biomasses suggest key roles of grazers in nutrient cycling and we estimate an export of ~ 50 Mt C yr −1 , solely from mortality of overwintering zooplankton that typically reside at depth. Deep lipid respiration (the lipid pump), for example, would increase this export even further. While inverted biomass pyramids prevailed at mid latitudes (50°–70°S), the balance of taxa differed regionally: for example, with biomass dominance by phytoplankton (highest latitudes and Pacific sector), mesozooplankton (Kerguelen Plateau), krill (north and east Scotia Sea), and salps (Crozet area). In light of contrasting climate change impacts between these sectors, we provide data that will underpin biogeochemical and food web models, blue carbon budgets, and the planning of marine protected areas.